ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU MANAJEMEN LABA PADA PERUSAHAAN TELEKOMUNIKASI DI ASIA TENGGARA TAHUN 2014-2017 - Alam Irwin Haldiaz; Dwi Ratmono (Diponegoro Journal of Accounting, 2019)
This study aims to analyze what factors influence earnings management in telecommunications firms in Southeast Asia in the period 2014-2017. The independent variables used in this study are firm’s  performance, firm’s size, and the level of financial leverage of a company. Earnings management is the dependent variable of this study. The hypothesis proposed in this study is that firm’s  performance and financial leverage have a positive effect on earnings management in telecommunications firms in Southeast Asia in the period 2014-2017, while firm size has a negative effect on earnings management practices in communication firm in Southeast Asia in the period 2014-2017The sample in this study consists of 95 telecommunications firms in Southeast Asia that reported their financial statements on the Bloomberg website in the period 2014-2017. The data used in this study are secondary data and the sampling used is purposive sampling method. To test the hypothesis, the technique of multiple linear regression analysis is used.The results of this study indicate firm’s size has a significant positive effect and financial leverage has a significant negative effect on earnings management. Company performance variables does not prove to significantly affect earnings management variables.